Evaluating a Conditional Cash Transfer Scheme in a Maternal Health Care Utilization Program Among Rural Pregnant Women in Mysore District, India - Sandra Kiplagat; Makella S. Coudray; Kavitha Ravi; Poornima Jayakrishna; Karl Krupp; Anjali Arun; Purnima Madhivanan (Women's Health Reports, 2020)
Background: According to the World Bank report in 2015, the maternal death rate in India was 174 per 100,000, which is among the highest in the world. The Indian Government launched the Janani Suraksha Yojana (JSY) conditional cash transfer program in 2005 to curb the adverse birth outcomes by promoting institutional delivery and providing antenatal care (ANC) services for pregnant women. This study evaluates the factors associated with JSY conditional cash transfer program in rural Mysore, India. Methods: Between 2011 and 2014, a prospective cohort study was conducted to examine the feasibility and acceptability of integrated ANC and HIV testing using mobile clinics in rural Mysore. Pregnant women in the Mysore Taluk provided an informed consent and answered an interviewer-administered questionnaire in local language, Kannada. All women underwent routine ANC services and were followed-up immediately after delivery, and 6 months and 12 months after delivery. Binary logistic regression was performed to identify factors associated with JSY benefits. Results: The mean age of the 1,806 mothers was 21.2???2.2 years and 58.9% of the mothers had primary education. Nearly half (51.6%) of the women reported having received JSY benefits. Factors associated with receiving JSY benefits included pregnant woman's partner not having any formal education (adjusted odds ratio [AOR]: 1.35; 95% confidence interval [CI]: 1.01?1.80), having income ?4,000 Indian Rupees (AOR: 1.47; 95% CI: 1.04?2.09), rare visits (once in 3 months visit) with Accredited Social Health Activists (AOR: 3.55; 95% CI: 1.55?8.51), and delivery in a public institution (AOR: 1.23; 95% CI: 1.01?1.51). Conclusions: While JSY has been operational in India since 2005, there continue to remain major gaps in the receipt of JSY services in rural India. Future interventions should include targeted services and expansion of JSY scheme, specifically among rural pregnant women, who are most at need of these services.